2021
DOI: 10.1093/ornithology/ukab025
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analyses reveal non-monophyly of the antbird generaHerpsilochmusandSakesphorus(Thamnophilidae), with description of a new genus forHerpsilochmus sellowi

Abstract: The family Thamnophilidae is a species-rich Neotropical radiation of passerine birds. Current classification of its 235 species is mostly based on morphological similarities, but recent studies integrating comprehensive phenotypic and phylogenetic data have redefined taxonomic limits of several taxa. Here, we assess generic relationships of Herpsilochmus, Sakesphorus, Thamnophilus, Biatas, and Dysithamnus using DNA sequences from the mitochondrion, nuclear exons, and ultraconserved elements, with further atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…In males, we observed that narrower banded songs (but not faster paced nor with grater performance) are associated with larger bills, but we did not detect an association between song frequency bandwidth and climate. Detection of a probable effect of climate on songs mediated by body size, but not by bills, may occur because antbirds show low variation in relative bill sizes, whereas body sizes are more variable (Gómez et al 2010;Bravo et al 2012Bravo et al , 2014Bravo et al , 2021. Our results suggest that climatic conditions may act as an integrative factor linking direct (e.g., habitat type) and indirect (e.g., morphology) sources of selection affecting acoustic signals.…”
Section: Traitsmentioning
confidence: 75%
See 3 more Smart Citations
“…In males, we observed that narrower banded songs (but not faster paced nor with grater performance) are associated with larger bills, but we did not detect an association between song frequency bandwidth and climate. Detection of a probable effect of climate on songs mediated by body size, but not by bills, may occur because antbirds show low variation in relative bill sizes, whereas body sizes are more variable (Gómez et al 2010;Bravo et al 2012Bravo et al , 2014Bravo et al , 2021. Our results suggest that climatic conditions may act as an integrative factor linking direct (e.g., habitat type) and indirect (e.g., morphology) sources of selection affecting acoustic signals.…”
Section: Traitsmentioning
confidence: 75%
“…2010; Bravo et al. 2012, 2014, 2021). We estimated bill surface area according to the formula: bill length × π × ((bill depth + bill width)/4) (Luther and Danner 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also classified species by endemism, conservation and migratory status. Species classification and nomenclature follow the Brazilian Committee of Ornithological Records (de Piacentini et al, 2015), and recent taxonomic and nomenclature changes (Bravo et al, 2021).…”
Section: Sampling Design and Data Classificationmentioning
confidence: 99%